TIMI flow and myocardial blushing after rescue PCI and cardiac magnetic resonance: Results from the Myocardial Salvage After Rescue Angioplasty: Evaluation by Magnetic Resonance (SAVE-ME) study. (15th December 2022) - Moroni, Francesco; Azzalini, Lorenzo; Caixeta, Adriano; Oliveira, Thiago P.; Ybarra, Luiz F.
Abstract: Introduction: Thrombolysis is currently reserved for ST-elevation myocardial infarction (STEMI) patients who cannot access timely percutaneous coronary intervention (PCI). In case of failed thrombolysis, rescue PCI is a viable option. Substantial data concerning the outcomes in terms of infarct size and myocardial function after rescue PCI are lacking. Methods: Forty patients treated with rescue PCI underwent serial contrast-enhanced cardiac magnetic resonance imaging (CMR) at 1 week, 3 months and 6 months from the index STEMI. Angiographic images were reviewed to assess Thrombolysis in Myocardial Infarction (TIMI) blood flow and TIMI Myocardial Blush Grade (TMBG) in the infarct related artery after PCI. Results: Patients with lower TMBG at the end of procedure, but not patients with worse TIMI flow, had lower left ventricular ejection fraction (LVEF) and higher volume of late gadolinium enhancement (LGE) on baseline CMR (44 ± 13% vs 52 ± 9%, p = 0.026, and 41 ± 21 ml vs 26 ± 12, p = 0.030, respectively). Patients with lower TMBG remained with significantly lower LVEF at 6 months follow up (48 ± 16% vs 59 ± 14, p = 0.049). Conclusion: TMBG after rescue PCI is associated with reduced LVEF and increased LGE burden. As TMBG is a known marker of microvascular damage after STEMI, novel strategies aimed at improving microvascular function in the setting of rescue PCI are needed to improve the outcomes in this patient population. Highlights: Data on infarct size and myocardial function after failed thrombolysis and rescue PCI are lacking. After rescue PCI, lower final TIMI blush grade was associated with lower LVEF and higher volume of late gadolinium enhancement. Novel strategies aimed at improving microvascular obstruction in the setting of rescue PCI are needed to improve outcomes.